The women of the Bible speak the wisdom of 16 women and their lessons for today - Bream, Shannon (New York Fox News Books, 2021)
People unfamiliar with Scripture often assume that women play a small, secondary role in the Bible. But in fact, they were central figures in numerous Biblical tales ... The Bible contains warriors like Jael, judges like Deborah, and prophets like Miriam. The first person to witness Jesus' resurrection was Mary Magdalene, who promptly became the first Christian evangelist ... In [this book], Fox News Channel's Shannon Bream opens up the lives of sixteen of these Biblical women, arranging them into pairs and contrasting their journeys. In pairing their stories, Shannon helps us reflect not only on the meaning of each individual's life, but on how they relate to each other and to us
Includes study guide questions.
Keywords: Women in the Bible--Biography.